2006
DOI: 10.1007/s11133-006-9012-2
|View full text |Cite
|
Sign up to set email alerts
|

Vice Careers: The Changing Contours of Sex Work in New York City

Abstract: In the mid-1990s, changes to law enforcement strategies in New York City pushed many women working in the sex trade off of the streets and into the indoors. Increasing numbers of women began advertising sexual services in bars, over the Internet, and in print media, and conducting their work in their homes, hotels, and brothels. This study uses indepth interviews and participant observation to examine the impact of this change on the life and work of women working in New York's indoor sex trade. A critical fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
80
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 36 publications
5
80
1
Order By: Relevance
“…21 The apparent growth in the indoor sex work industry has been traced in part to more aggressive policing of street-based sex workers, driving sex work into indoor venues, and use of the Internet to connect clients and sex workers. 19 We briefly summarize the literature that provides two possible conceptual explanations for clustering: (1) cost-reduction advantages associated with localization and urbanization economies and (2) lower levels of law enforcement monitoring associated with moderate-and higherincome neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The apparent growth in the indoor sex work industry has been traced in part to more aggressive policing of street-based sex workers, driving sex work into indoor venues, and use of the Internet to connect clients and sex workers. 19 We briefly summarize the literature that provides two possible conceptual explanations for clustering: (1) cost-reduction advantages associated with localization and urbanization economies and (2) lower levels of law enforcement monitoring associated with moderate-and higherincome neighborhoods.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Few studies have focused on indoor sex work businesses outside of red-light districts, leaving gaps in knowledge about health for female sex workers and their male clients. 15,19 One study has suggested, for example, that sex work outside of red-light districts is associated with increased pressure on female sex workers to not use condoms. 20 …”
mentioning
confidence: 99%
“…We include dummies for the wave 2 (2007) and wave 3 (2009) surveys (reference = 2006). Because venue is a central stratifier (Murphy and Venkatesh 2006;Sanders et al 2009;Weitzer 2009), we include dummies indicating if the FSW worked in a brothel, street, lodge, or highway (reference = home).…”
Section: Independent Variablesmentioning
confidence: 99%
“…This literature highlights the role of human capital, and the prices for beauty, condom usage, and particular sex acts. In the past decade or so, the sociological literature on the work of sex work has also grown rapidly (e.g., Bernstein 2007;Boris, Gilmore, and Parrenas 2010;Brents, Jackson, and Hausbeck 2010;Lever and Dolnick 2010;Murphy and Venkatesh 2006;Oselin and Blasyak 2013;Rosen and Venkatesh 2008;Sanders 2005;Sanders et al 2009). The sociological literature goes beyond purely economic factors to investigate gender, social relations, stigma, and legality.…”
mentioning
confidence: 99%
“…As ethnography is (re)gaining a well-deserved prominence within the discipline its empirical focus, theoretical underpinnings, and narrative styles are also expanding -traditional forms of ethnographic inquiry now coexist with more experimental ones. From dealing drugs (Bourgois 1995), to emigrating and immigrating (Fitzgerald 2006;Smith 2006), prostituting (Murphy and Venkatesh 2006), working off the books (Venkatesh 2006), boxing (Wacquant 2003a), dancing (Wainwright et al 2005), glassblowing (O'Connor 2006), designing objects (Molotch 2005), providing services in luxury hotels (Sherman 2007), and street vending (Duneier 2000) the list of activities and subjects upon which ethnography has focused its attention in recent years is virtually inexhaustible. Ethnographers have been heeding Park's advice: they have gotten the seat of their pants dirty in a myriad of places, researching all sorts of (more or less exotic) practices.…”
mentioning
confidence: 99%